50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3854
|View full text |Cite
|
Sign up to set email alerts
|

PECyT - Plasma Enhanced Cycloidal Thruster

Abstract: In the following paper we introduce PECyT system for enhancing the aerodynamic efficiency of cycloidal rotors. For that purpose the incorporation of Dielectric Barrier Discharge plasma actuators for active flow control on a pitching airfoil, under deep-stall conditions, will be assessed using a numerical tool. Two different arrangements of DBD actuators will be analysed, namely single- and multi-DBDs configurations. For the single- DBD plasma actuator the effect of different modes of actuation on the lift coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Previous results have shown that the influence of the DBDs on each other is additive and our CFD results [33] have shown that, the Multi-DBD system will causes ionic wind with higher intensity. To confirm this and to better understand how a multi-DBD actuator is more effective than a single DBD actuator, Fig.…”
Section: Resultsmentioning
confidence: 51%
“…Previous results have shown that the influence of the DBDs on each other is additive and our CFD results [33] have shown that, the Multi-DBD system will causes ionic wind with higher intensity. To confirm this and to better understand how a multi-DBD actuator is more effective than a single DBD actuator, Fig.…”
Section: Resultsmentioning
confidence: 51%
“…To this end, data for a cyclogyro of similar dimensions as the wind turbine, operating in propulsion mode (V wind = 0), is used. This configuration, here denominated IAT21-L3 rotor, was analysed as a part of a major European ongoing project, which aims to develop the cyclogyro technology as a mean of propulsion for small and medium size aircraft [12,[15][16][17][18][19]. It is obvious that the results obtained for the IAT21-L3 rotor does not faithfully represent the features of a VAWT, since in propulsion mode energy is being provided and not extracted from the flow.…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…In order to verify its generality, the equation was tested using data from alternative rotors. 22,36 These rotors are different in size and maximum pitch angle from the first rotor that was used to determine equation (28). Figure 20 shows a slope value of E at different pitching conditions as a function of rotating speed.…”
Section: Kinematic Analysismentioning
confidence: 99%
“…Thrust coefficient as a function of rotor angular velocity, comparison between experimental and analytic results-IAT21 case 36. …”
mentioning
confidence: 99%
See 1 more Smart Citation